Popperian ecology is a delusion - Jani Raerinne (Ecology and Evolution, 2024)
Abstract During the last 50 years, a group of ecologists has repeatedly used Popper's falsificationism in normative claims concerning how research in ecology should be conducted and/or how ecology should be corrected. Other ecologists seem to be dissatisfied with these criticisms. Nevertheless, they have not provided systematic analyses of how and why the Popperian criticisms of ecology fail. I have two aims in this article First, I show how so‐called Popperian ecologists have not only failed to use but have misused – if not abused – Popper in their criticisms of ecology. That is, the Popperian criticisms of ecology lack the justification the critics claim it has. Second, I claim that Popper's falsificationism is an unsuitable philosophy of science for ecology. In other words, ecology should not be criticized nor evaluated from the Popperian perspective in the first place.